Prevalence of HIV and hepatitis B coinfection in Ghana: a systematic review and meta-analysis - Agyeman, Akosua Adom (AIDS Res Ther, 2016)
BACKGROUND: Human immunodeficiency virus (HIV) and hepatitis B virus (HBV) coinfection has been associated with higher morbidity and mortality and may impact significantly on healthcare resource utilization. However, in Ghana, accurate estimates of the prevalence of HIV/HBV coinfection needed to inform policy decisions and the design of public health interventions are currently lacking. In this study, our aim was to determine the HIV/HBV coinfection prevalence rate in Ghana. METHODS: Primary studies reporting prevalence of HIV/HBV coinfection in Ghana were retrieved through searches conducted in PubMed, science direct, Google scholar and Africa journals online (AJOL) databases. The websites of the Ministry of Health and Ghana Health Service were also searched for related reports or reviews. Additionally, the online repository of two leading Ghanaian universities were searched to identify unpublished thesis related to the subject. All online searches were conducted between 01/03/2016 and 12/03/2016. Further searches were conducted through reference screening of retrieved papers. RESULTS: Twelve (12) studies published between 1999 and 2016 and conducted across seven (7) regions of Ghana were included in this review. The three (3) regions with no studies’ representation were Upper East, Upper West and Central regions. The 12 included studies involved a total of 8162 HIV patients. The reported HIV/HBV coinfection prevalence rates ranged from 2.4 to 41.7 %. The pooled HIV/HBV coinfection prevalence rate was determined as 13.6 % (95 % CI 10.2–16.8 %; P < 0.001). CONCLUSIONS: In Ghana, about one in seven HIV patients may be also be chronically infected with HBV. Preventive interventions and strategic policy directions including systematic screening of all newly diagnosed HIV cases for coinfection will be needed, so as to improve management strategies for HBV infection and antiretroviral therapy (ART) implementation.